2015
DOI: 10.3390/molecules20058395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antifungal Activity and Structure-Activity Relationships of Novel 3-(Difluoromethyl)-1-methyl-1H-pyrazole-4-carboxylic Acid Amides

Abstract: A series of novel 3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxylic acid amides were synthesized and their activities were tested against seven phytopathogenic fungi by an in vitro mycelia growth inhibition assay. Most of them displayed moderate to excellent activities. Among them N-(2-(5-bromo-1H-indazol-1-yl)phenyl)-3-(difluoro-methyl)-1-methyl-1H-pyrazole-4-carboxamide (9m) exhibited higher antifungal activity against the seven phytopathogenic fungi than boscalid. Topomer CoMFA was employed to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
0
32
0
2
Order By: Relevance
“…Besides, structure-activity relationship was discussed in this paper. 21 Testing the inhibitory properties of [2-(1-aryl-1H-1,2,4-triazol-3-yl)phenyl](heterylmethyl)amines 70 toward VEGF-1 and VEGF-2 receptors showed that compound with 3-fluoro(bromo, tert-butyl)phenyl substituents and 4-pyridyl fragment had IC 50 of 0.046-0.13 μM. 32 The molecular docking studies with VEGF receptor inhibitor vatalanib as reference have shown that lead compounds were the promising anticancer drugs.…”
Section: Biological Properties Of 2-(azolyl)anilinesmentioning
confidence: 97%
See 2 more Smart Citations
“…Besides, structure-activity relationship was discussed in this paper. 21 Testing the inhibitory properties of [2-(1-aryl-1H-1,2,4-triazol-3-yl)phenyl](heterylmethyl)amines 70 toward VEGF-1 and VEGF-2 receptors showed that compound with 3-fluoro(bromo, tert-butyl)phenyl substituents and 4-pyridyl fragment had IC 50 of 0.046-0.13 μM. 32 The molecular docking studies with VEGF receptor inhibitor vatalanib as reference have shown that lead compounds were the promising anticancer drugs.…”
Section: Biological Properties Of 2-(azolyl)anilinesmentioning
confidence: 97%
“…Exhaustive research of antifungal activity using molecular docking was conducted by Du, 21 and it was found that 1-methyl-N-[2-(1H-heteryl)phenyl]-3-(difluoromethyl)-1H-pyrazole-4-carboxamides 53 inhibited the growth of Сolletotrichum orbiculare, Rhizoctonia solani, Phytophthora infestans, Pythium aphanidermatum, Fusarium moniliforme, Botryosphaeria berengeriana, and Botrytis cinerea up to 17-94%. Molecules bearing the 1-indazole and 5-bromo-1-indazole fragments were the most effective (IC 50 5.5-96 μg/ml) exceeding the reference fungicide boscalid (2-chloro-N-(4'-сhlorobіphenyl-2-yl)-nicotinamide).…”
Section: Biological Properties Of 2-(azolyl)anilinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, heterocyclic compounds play an important role in organic chemistry , medicinal chemistry , pesticidal chemistry , and inorganic chemistry . Among them, five membering pyrazole compounds had been considerably used in synthetic medicines and pesticides , as they possessed diversity biological activities, such as herbicidal , anti‐tobacco mosaic virus , insecticidal , antimicrobial , antioxidant , antifungal , xanthine oxidase inhibitory , and anti‐inflammatory activity . Some pyrazole compounds have been developed as commercial drugs and pesticides, such as tebufenpyral, fipronil, fenpyroximate, tolfenpyrad, and chlorantraniliprole.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bioassays have shown that some target molecules exhibited good antifungal activities against Rhizoctonia solani, Botrytis cinerea and Pythium aphanidermatum. By comparing the structure and activity, we found that amides with indazole groups have high antibacterial activity.…”
Section: -(4'-chloro-[11'-biphenyl]-2-yl)nicotinamide)mentioning
confidence: 99%